AN APPLIED MODEL OF TEACHING MATERIALS TO IMPROVE STUDENTS’ SPEAKING SKILL - Rajab, Tarmizi (SCAD Independent, 2015)
An Applied Model of Teaching Materials to Improve Students’ Speaking Skill showed the best results of the experimental study done to the students of the English Study Program of Teacher Training and Educational Science Faculty Serambi Mekkah University Banda Aceh. The subject was specifically applied to the students of the mentioned institution, in terms of finding out its impact to the teaching-learning process of students’ speaking skill referred to the principles of language teaching. The main target of this study is to produce the teaching materials in the form of textbook; therefore, it is done in three years. The first year was focused on preparing the research instrument. The second year will be concerned with all kinds of revising the instrument. While the last year will get various kinds of data to revise the teaching materials to become simple, practical, and applicable handbook labelled of Book-ISBN branded for the speaking class.